Environment‐Dependent Adhesive Behaviors of Mussel‐Inspired Coordinate‐Crosslinked Bioadhesives - Sidi Li; Ning Chen; Yang Li; Jin Zhao; Xin Hou; Xubo Yuan (Macromolecular Materials and Engineering)
Abstract Mussel‐inspired, coordinate‐crosslinked gels have attracted extensive attention but their adhesive behaviors are still not fully understood. Herein, four mussel‐inspired molecules with different molecular characteristics are synthesized to study their adhesive behaviors. It is demonstrated that their adhesive behaviors are dependent on the environments. For these mussel‐inspired molecules, physiological environment containing relatively low Fe3+ contents is appropriate for achieving high adhesive strength. In addition, the mussel‐inspired molecules with positive charge, high molecular weight, or high catechol substitute ratio benefited for improving adhesive strength, however, only in the appropriate environment. In the inappropriate environments (physiological pH, high Fe3+ contents), the adhesives show similar low adhesive strength. These environment‐dependent adhesive behaviors are due to the poor interfacial adhesive capacity of the adhesives formed in the inappropriate environments. The study uncovers the adhesive behaviors of mussel‐inspired coordinate‐crosslinked gels and thus may further provide valuable evidences in the design of metal‐crosslinked bioadhesives.